Potential Role of CD99 Signaling Pathway in Schwann Cell Dysfunction in Diabetic Foot Ulcers Based on Single-Cell Transcriptome Analysis - Yannan Zhou; Yaxin Zhou; Haohan Chen; Li Zhang; Siwei Bi (Journal of Diabetes Research)
Conclusion: Our study elucidated that the CD99 pathway activation may play a crucial role in SC dysfunction of DFU, providing insights into the peripheral glia regulation mechanism and potential therapeutic target of DFU.